Complications of lateral plate fixation compared with tension band wiring and pin or lag screw fixation for calcaneoquartal arthrodesis - Barnes, D. C.; Knudsen, C. S.; Gosling, M.; McKee, M.; Whitelock, R. G.; Arthurs, G. I.; Ness, M. G.; Radke, H.; Langley-Hobbs, S. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
Objective: To compare complication rates and the outcomes of these complications after lateral plate fixation with figure-ofeight tension-band-wire and pin or lag screw fixation for arthrodesis of the calcaneoquartal joint, following non-traumatic disruption of the plantar tarsal ligament in dogs.Methods: Data were collected retrospectively from five UK referral centres. Diplomate specialists and their residents performed all procedures. Referring veterinarians were contacted for long-term follow-up.Results: Seventy-four procedures were undertaken in 61 dogs. There were 58 arthrodeses in the lateral plate group (Plate), nine in the pin and tension-band-wire group (Pin), and seven in the lag screw and tension-band wire-group (Screw). Compared to Plate (17%), further surgical intervention was required more frequently following Pin (56%, OR = 3.2) or Screw (43%, OR = 2.5) fixation. Clinical failure of arthrodesis occurred less frequently with Plate (5%) compared with Screw (43%, OR = 8.6) and Pin fixation (22%, OR = 4.4). Cases managed with external coaptation postoperatively were more likely to suffer from postoperative complications (OR = 2.2).Clinical significance: Lateral plating was associated with fewer postoperative complications than pin and tension-band-wire fixation for arthrodesis of the calcaneoquartal joint in dogs with non-traumatic disruption of the plantar tarsal ligament.
Keywords: Plantar tarsal ligament; calcaneoquartal arthrodesis; plate; tension-band-wire